2019
DOI: 10.1186/s41476-019-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

An auxiliary field approach for computing optical resonances in dispersive media

Abstract: We report on an auxiliary field approach for solving nonlinear eigenvalue problems occurring in nano-optical systems with material dispersion. The material dispersion can be described by a rational function for the frequency-dependent permittivity, e.g., by a Drude-Lorentz model or a rational function fit to measured material data. The approach is applied to compute plasmonic resonances of a metallic grating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[ 80 ] By carefully studying the trajectories of zeros, we prove that the boundaries of the 2π phase change regions correspond to EPs where two transmission zeros become degenerated. We also computed the electric and magnetic resonance frequencies of this Sb 2 S 3 metasurface by solving eigen‐value problems, [ 81 ] and the silicon nanodisk metasurface proposed in ref. [24] (see Supporting Information), and we found that they never fully coincide.…”
Section: Explicit or Spontaneous Symmetry‐breaking Leading To 2π‐phas...mentioning
confidence: 99%
“…[ 80 ] By carefully studying the trajectories of zeros, we prove that the boundaries of the 2π phase change regions correspond to EPs where two transmission zeros become degenerated. We also computed the electric and magnetic resonance frequencies of this Sb 2 S 3 metasurface by solving eigen‐value problems, [ 81 ] and the silicon nanodisk metasurface proposed in ref. [24] (see Supporting Information), and we found that they never fully coincide.…”
Section: Explicit or Spontaneous Symmetry‐breaking Leading To 2π‐phas...mentioning
confidence: 99%
“…These results were derived by solving an eigenvalue problem where outgoing boundary conditions were imposed in the regions at the top and bottom of the metasurface. These calculations were performed using the eigenvalue solver implemented in JCMsuite [71].…”
Section: Siv Real and Complex Frequency Numerical Calculationmentioning
confidence: 99%